2021
DOI: 10.1002/joc.7159
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal differences and uncertainties in projections of precipitation and temperature in South Korea from CMIP6 and CMIP5 general circulation models

Abstract: This study compared the historical simulations and future projections of precipitation and temperature of Coupled Model Intercomparison Project (CMIP)5 and CMIP6 general circulation models (GCMs) to quantify the differences in the projections due to differences in scenarios. Five performance indicators were used to quantify the model reproducibility of the observed precipitation levels at 22 stations for the historical period of 1970–2005. The percentages of change in precipitation and temperature were estimat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 60 publications
(35 citation statements)
references
References 65 publications
0
34
0
1
Order By: Relevance
“…Afterwards, correction factors were applied to correct the bias in the projected data (2020–2100) at each station. The QM method has been concluded as effective for bias corrections of GCM simulations in South Korea (Song et al, 2020; Song et al, 2021b).…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, correction factors were applied to correct the bias in the projected data (2020–2100) at each station. The QM method has been concluded as effective for bias corrections of GCM simulations in South Korea (Song et al, 2020; Song et al, 2021b).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a new phase model, the Coupled Model Intercomparison Project (CMIP) Phase 6 based on the shared socioeconomic pathways (SSPs) reflecting socioeconomic factors have been released. Song, Chung and Shahid (2021) compared the uncertainty of future temperature based on both SSPs and RCPs scenarios, and the results showed that the uncertainty in Korea was lower for SSPs than for RCPs. Therefore, to project the future WUR and WA using new scenarios for SSP, the DBN based model proposed in this study can be applied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu and Yang (2020) showed lower performance of CMIP6 MME in the wet region of the Tibetan Plateau. Song et al (2021a) showed higher uncertainty in projections for SSPs compared to RCPs. Srivastava et al (2020) showed similar bias in both CMIPs in reproducing climatology over the United States.…”
Section: Introductionmentioning
confidence: 93%
“…(2021) reported better capacity of CMIP6 GCMs in reproducing Southern Hemisphere westerlies. However, the lower or similar performance of CMIP6 GCMs compared to CMIP5 GCMs has also been reported in several studies (Srivastava et al ., 2020; Zhu and Yang, 2020; Song et al ., 2021a). Zhu and Yang (2020) showed lower performance of CMIP6 MME in the wet region of the Tibetan Plateau.…”
Section: Introductionmentioning
confidence: 99%